Incidence and correlates of testicular pain after kidney donation - Gandhi, Nisarg V.; Murad, Dina N.; Hebert, Sean A.; Morgan, Monica; Nguyen, Duc T.; Graviss, Edward A.; Ibrahim, Hassan N. (Frontiers in Urology, 2022)
Some kidney donors experience testicular pain after donation. We studied the presence of testicular pain in male donors from The Renal and Lung Donor Evaluation (RELIVE) Study which investigated short- and long-term outcomes of 8922 kidney donors. Of the 2551 male donors with available testicular status data included in the analysis, 54 (2.12%) developed testicular pain 19 days (IQR 7, 40) after donation: 34 had testicular pain only, 6 had epididymitis, and 14 had both. Donors developing pain were 4 years older and pain occurred more often in those undergoing laparoscopic nephrectomy; 3.6% vs. 1.1% for open nephrectomy. Non-Hispanic White ethnicity and undergoing laparoscopic nephrectomy were associated with increased risk of testicular pain; RR 5.56 (95% CI 1.35, 22.84), p=0.02, RR 3.11 (95% CI 1.71, 5.65), p<0.001, respectively. Laterality of nephrectomy, however, was not associated with increased risk of testicular pain. Testicular pain is not infrequent and contrary to previous reports, left nephrectomy was not associated with a higher incidence of testicular pain. Donors should be routinely asked about this potentially bothersome complication.